Analgesic Efficacy of Ketoprofen Transdermal Patch versus Ibuprofen Oral Tablet on Postendodontic Pain in Patients with Irreversible Pulpitis: A Randomized Clinical Trial - Saeede Zadsirjan; Amirhossein Toghrolian; Nazanin Zargar (Pain Research and Management)
Background and Aim. Pain control is an integral part of dental treatment. The majority of patients complain of pain after endodontic procedures. Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly prescribed for postoperative pain management and are available in various forms. Ketoprofen transdermal patch (KTP) has been limitedly investigated for pain control after endodontic treatments. The aim of this study was to compare the efficacy of KTP versus ibuprofen tablets for pain control after single-visit endodontic treatment of mandibular molars with irreversible pulpitis. Materials and Methods. In this randomized clinical trial, 64 patients who had mandibular first and second molars with irreversible pulpitis were randomly divided into two groups (n = 32) by stratified permuted block randomization. The experimental group used 60 mg KTP every 6 hours, and the control group received 400 mg ibuprofen tablets every 6 hours for 1 day. The severity of pain experienced by patients was quantified before and at 2, 4, 8, 12, 24, and 48 hours after endodontic treatment, using the numerical rating scale (NRS). Data were analyzed by using the t-test, Mann–Whitney test, and generalized estimating equation (GEE) (alpha = 0.05). Results. The pain score was not significantly different between the two groups at the baseline or any other postoperative time point (P>0.05). The reduction in the pain score was significant in both groups from 2 to 10 hours and 10 to 48 hours, postoperatively (P<0.001). The interaction effect of time and group was not significant on the postoperative pain score in the abovementioned time intervals, and the pattern of pain reduction was the same over time in both groups (P>0.05). Conclusion. Both KTP and ibuprofen effectively decreased postendodontic pain. Considering the comparable pattern of pain reduction, KTP can be used as an alternative to ibuprofen tablets for effective pain control after endodontic treatment of mandibular first and second molars with irreversible pulpitis.